Relate oral health and physical fitness in industrial direct labor workers: pilot study. - Labrador, Alejandro; Burgos Navarrete, Francisco José; Escalona, Evelin; Chaparro, Estefanía (Conexiones UG, 2023)
Physical fitness is the ability of a person to be able to do physical work effectively and without excessive fatigue. In some jobs, physical fitness is a threshold physiological competency. Objective: To relate oral health versus physical fitness in a population of direct labor workers in the Venezuelan industrial sector. Methods: Field study, quantitative, correlational, cross-sectional, epidemiological. Population: industrial direct labor workers, in which a pilot test was taken with a sample of 60 workers (36 men-24 women): A prior oral check-up was carried out and then physical fitness tests were carried out: push-ups or chest push-ups; sit-ups in 1 minute, and reps in 1 minute of standing up and sitting down. Results: The female population (24 subjects) with an average of 40.97±12.64 years of age. 63% have oral health problems specifically periodontitis. Male population with average age: 44.88±13.78 years, the percentage of workers with periodontitis 67%. It can be concluded that there is a first approximation in the relationship between oral health and physical fitness in the parameters of heart rate at rest and relative aerobic capacity in male workers.
Keywords: Physical fitness; oral health workplace; heart rate; periodontitis; dental caries